Pulmonary embolism and subclavian vein thrombosis in a patient with parathyroid carcinoma: Case report and review of literature - Worapaka Manosroi (2018)
© 2015, Medical Association of Thailand. All Rights reserved. Parathyroid carcinoma is a rare etiology of primary hyperparathyroidism responsible for 0.4 to 5.2% of all primary hyperparathyroidism cases. The overt hyperparathyroid bone or renal disease with palpable neck mass, as well as severe hypercalcemia with extremely high parathyroid hormone, are clinical parameters raising the suspicion for parathyroid carcinoma. However, a definite diagnosis can be confirmed only by examining the histopathology of the tumor. The curative treatment solely depends on an en bloc surgical approach. Therefore, preoperative clinical diagnosis of carcinoma is essential for optimal surgical planning. The present study reported asymptomatic subclavian vein thrombosis and pulmonary embolism in parathyroid carcinoma, suggesting paraneoplastic syndrome of hypercoagulability in this cancer type. The presence of this paraneoplastic syndrome in a case of overt clinical hyperparathyroidism in addition to a palpable neck mass indicated the diagnosis of carcinoma preoperatively in the present patient, which led to an en bloc surgical plan. Since this paraneoplastic syndrome can be asymptomatic, the exploration of this syndrome by a commonly used imaging technique for parathyroid tumor localization, computerized tomography, would enable a preoperative diagnosis of cancer, especially in an equivocal situation.